TYPES OF MALIGNANT PESTS DAMAGING AGRICULTURAL PRODUCTS DURING THE STORAGE PERIOD (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article provides information on the types of pests that affect stored products during storage and the damage they cause.